Prioritas Pengembangan Objek Agrowisata Balai Benih Induk (BBI) Kelurahan Lubuk Minturun Kecamatan Koto Tangah Kota Padang - Nasarta, Bima; Wilis, Ratna (Lembaga Yasin AlSys, 2025)
The Agrotourism site of the Balai Benih Induk (BBI) Lubuk Minturun, located in Koto Tangah District, Padang City, holds considerable potential that has yet to be optimally managed to support sustainable tourism development. This study aims to identify the characteristics of the BBI Lubuk Minturun agrotourism site and to formulate strategies for its sustainable development. A descriptive qualitative approach was employed, utilizing data triangulation techniques through observation, documentation, and in-depth interviews. Data were analyzed descriptively and through the SOAR (Strengths, Opportunities, Aspirations, Results) framework. The findings indicate several priority strategies, including the implementation of entrance fees, installation of directional signage, agricultural training programs, digital promotion through social media and website development, optimization of fishpond and cafeteria functions through management training, development of culinary tourism and souvenir products, and provision of supporting services such as Wi-Fi, waste bins, and waste management training. The study concludes that development strategies grounded in local potential and active community participation are essential to realizing BBI Lubuk Minturun as a leading, competitive, and sustainable agrotourism destination.